The Environmental Impact of Cattle Access to Watercourses: A Review. Issue 2 (1st March 2019) - O'Callaghan, Paul; Kelly‐Quinn, Mary; Jennings, Eleanor; Antunes, Patricia; O'Sullivan, Matthew; Fenton, Owen; hUallacháin, Daire Ó.
Abstract : The degradation of freshwater resources and loss of freshwater biodiversity by anthropogenic activities, including agriculture, are of major global concern. Together with diffuse pollutants, point sources, such as where cattle have direct access to riparian margins and watercourses, can potentially present significant environmental challenges. These can include impacts on stream morphology, increased sedimentation, nutrient additions, microbial contamination, and impacts on aquatic biota. Mitigation measures aimed at reducing these frequently include reducing the amount of time cattle spend in riparian margins and watercourses. This is often accomplished through the provision of an alternative water supply and grazing management, or even cattle exclusion measures. Although a number of studies refer to potential negative impacts, there has been little attempt to review previous research on this topic. The key aim of this paper is to collate and review these disparate studies, as well as those relating to the effectiveness of mitigation measures. Although it is difficult to draw generalizations from studies due to the inherent variability between and within catchments, evidence pertaining to impacts in relation to sedimentation, pathogens, and riparian margin vegetation were strong. Conclusions in relation to impacts on stream morphology and nutrient parameters were less clear, whereas studies on responses of macroinvertebrate communities were particularly variable, with differences due to cattle access difficult to separate from catchment scale effects. A greater understanding of the impact of cattle access on watercourses under varying conditions will help inform policymakers on the cost effectiveness of existing management criteria and will help in revising existing measures. Core Ideas: It has been hypothesized that direct cattle access to waterways can result in impacts to streams. Little effort has been made to collate information on the efficacy of mitigation measures. Divergent results on the effect of cattle access on various parameters highlight the need for further research.